Mitochondrial targeted doxorubicin derivatives delivered by ROS-responsive nanocarriers to breast tumor for overcoming of multidrug resistance. (2nd January 2021) - Zhong, Xin-Cheng; Shi, Ming-Han; Liu, Hui-Na; Chen, Jie-Jian; Wang, Tian-Tian; Lin, Meng-Ting; Zhang, Zhen-Tao; Zhou, Yi; Lu, Yi-Ying; Xu, Wen-Hong; Gao, Jian-Qing; Xu, Dong-Hang; et al.
Abstract: Multidrug resistance (MDR) is a serious challenge in chemotherapy and also a major threat to breast cancer treatment. As an intracellular energy factory, mitochondria provide energy for drug efflux and are deeply involved in multidrug resistance. Mitochondrial targeted delivery of doxorubicin can overcome multidrug resistance by disrupting mitochondrial function. By incorporating a reactive oxygen species (ROS)-responsive hydrophobic group into the backbone structure of hyaluronic acid – a natural ligand for the highly expressed CD44 receptor on tumor surfaces, a novel ROS-responsive and CD44-targeting nano-carriers was constructed. In this study, mitochondria-targeted triphenylphosphine modified-doxorubicin (TPP-DOX) and amphipathic ROS-responsive hyaluronic acid derivatives (HA-PBPE) were synthesized and confirmed by 1 H NMR. The nanocarriers TPP-DOX @ HA-PBPE was prepared in a regular shape and particle size of approximately 200 nm. Compared to free DOX, its antitumor activity in vitro and tumor passive targeting in vivo has been enhanced. The ROS-responsive TPP-DOX@HA-PBPE nanocarriers system provide a promising strategy for the reverse of MDR and efficient delivery of doxorubicin derivatives into drug-resistant cancer cells.